Special structures of hoopoe eggshells enhance the adhesion of symbiont‐carrying uropygial secretion that increase hatching success. (28th May 2014) - Martín‐Vivaldi, Manuel; Soler, Juan J.; Peralta‐Sánchez, Juan M.; Arco, Laura; Martín‐Platero, Antonio M.; Martínez‐Bueno, Manuel; Ruiz‐Rodríguez, Magdalena; Valdivia, Eva; Ardia, Daniel
Summary Animals live in a bacterial world, and detecting and exploring adaptations favouring mutualistic relationships with antibiotic‐producing bacteria as a strategy to fight pathogens are of prime importance for evolutionary ecologists. Uropygial secretion of European hoopoes (Upupa epops, Linnaeus) contains antimicrobials from mutualistic bacteria that may be used to prevent embryo infection. Here, we investigated the microscopic structure of hoopoe eggshells looking for special features favouring the adhesion of antimicrobial uropygial secretions. We impeded female access to the uropygial gland and compared microscopic characteristics of eggshells, bacterial loads of eggs and of uropygial secretion, and hatching success of experimental and control females. Then, we explored the link between microbiological characteristics of uropygial secretion and these of eggs of hoopoes, as well as possible fitness benefits. The microscopic study revealed special structures in hoopoes' eggshells (crypts). The experimental prevention of females' gland access demonstrated that crypts are filled with uropygial secretion and that symbiotic enterococci bacteria on the eggshells come, at least partially, from those in the female's uropygial gland. Moreover, the experiment resulted in a higher permeability of eggshells by several groups of bacteria and in elimination of the positive relationships detected for control nests between hatching success and density of symbiotic bacteria, either in the uropygial secretion of females or on the eggshell. The findings of specialized crypts on the eggshells of hoopoes, and of video‐recorded females smearing secretion containing symbiotic bacteria at a high density onto the eggshells strongly support a link between secretion and bacteria on eggs. Moreover, the detected associations between bacteria and hatching success suggest that crypts enhancing the adhesion of symbiont‐carrying uropygial secretion likely protect embryos against infections.